O direito e o caso : aportes para uma teoria do precedente judicial no Brasil - Rocha, Vinícius Andrade de Carvalho (2018)
This work advances a reinterpretation of the history of the development of Law in Western civilization, considering some aspects that have resulted in a significant gap between common law and civil law legal traditions. This gap is approached from the perspective of the legal rationalities that each of those traditions began to value at some point. In the case of the common law, we highlight the predominance of a rationality that honors the empirical reality and the adoption of techniques which value inductive models of reasoning. In this sense, we consider that some of those aspects can be of special usefulness in the context of reforms in Brazil’s civil procedural system. To exemplify the mechanics of precedent in a concrete legal situation, we conduct a case study of the transcripts of the oral arguments in Masterpiece Cakeshop v. Colorado Civil Rights Commission, awaiting deliberation by the United States Supreme Court. We consider, nevertheless, some obstacles to the applicability of those traits within the Brazilian legal system: the first one, which has an operational nature, concerns the individualistic attitude of the judge; the second, which has a technical nature, refers to the legal uncertainty that the method of ‘balance of interests’ can promote in legal systems that grant binding force to judicial precedents. In order to synthesize all the ideas discussed, we offer an instrument, in the form of a scale, to measure the potential of a given judicial decision to constitute a judicial precedent. Lastly, we apply the proposed scale to the decision of the Brazilian Supreme Court in the judgment of Complaint 4.335/AC, aiming to assess its practical feasibility.